Influence of cross-linkers on ezrin-bound minimal actin cortices. (July 2019) - Schön, Markus; Mey, Ingo; Steinem, Claudia
Abstract: The actin cortex is a thin network coupled to the plasma membrane of cells, responsible for e.g., cell shape, motility, growth and division. Several model systems for minimal actin cortices (MACs) have been discussed in literature trying to mimic the complex interplay of membrane and actin. We recapitulate on different types of MACs using either three dimensional droplet interfaces or lipid bilayers to which F-actin networks are attached to or planar lipid bilayers with bound actin networks. Binding of the network to the membrane interface significantly influences its properties as well as its dynamics. This in turn also influences, how cross-linkers as well as myosin motors act on the network. Here, we describe the coupling of a filamentous actin network to a model membrane via the protein ezrin, a member of the ezrin-radixin-moesin family, which forms a direct linkage between the plasma membrane and the cortical web. Ezrin binding to the membrane is achieved by the lipid PtdIns(4, 5)P2, while attachment to F-actin is mediated via the C-terminal domain of the protein leading to a two dimensional arrangement of actin filaments on the membrane. Addition of cross-linkers such as fascin and α-actinin influences the architecture of the actin network, which we have investigated by means of fluorescence microscopy. The results are discussed in terms of the dynamics of the filaments on the membrane surface.